শহীদ জননী জাহানারা ইমাম স্বারকগ্রন্থ - Riṭana, Lut̲phara Rahamāna
Commemorative volume on Jāhānāra Imāma, woman political activist from Bangladesh; comprises articles, poems, and sketches on her life and activities.